The chronicle and Peruvian traditions: the reworking of events and adventures - Huárag Álvarez, Eduardo (2019)
This essay explores how the interrelations between the chronicles of the Inca Garcilaso de la Vega and the Palentino and the Peruvian Traditions of Ricardo Palma take place. It would be a question of investigating the degree of dependence of Palma with the chronicles of the mentioned authors and in what aspects there is such a relationship. Thus, when making the analysis of several traditions, we will find the links of the traditions with the approach of the chronicle, but in turn, it can be perceived that there is a process of mutation or adaptation that makes Palma’s style particular. Certainly, anecdotal episodes in the chronicles are not the central purpose in the chronicler; while for Palma, each episode constitutes an autonomousstory, with structure and treatment that requires a short story.